Examining the effect of online information-seeking and searching behaviours on the academic performance of undergraduate university students - Ahmad, Dr. Sajjad; Sami Ullah,; Sohail, Muhammad; Ahmad, Dr. Shehzad (IJoLIS, 2025)
Purpose: This study investigates how online information-seeking and searching behaviors influence the academic performance of undergraduate students at the University of Peshawar. It highlights the significance of effective search practices and students’ perceptions of online information in enhancing academic outcomes. Design/methodology/approach: A stratified random sampling technique was employed, selecting two departments from each faculty to ensure balanced representation. Data were collected through a validated 5-point Likert scale questionnaire. Of the 523 distributed surveys, 315 were filled, resulting in a 60.2% response rate. Data analysis was conducted using SPSS version 30.0 to examine students’ information-seeking patterns, search strategies, and perceived quality of online information. Research limitations: The study was limited to undergraduate students from a single institution, which may restrict the generalizability of the findings. Moreover, the use of self-reported data may introduce response bias. Key findings: Social media emerged as the most frequently accessed online source, with 73.0% of respondents using it daily, followed by Google search engines (53.7%) and Wikipedia (34.9%). Boolean operators were identified as the most commonly applied search strategy (M = 3.68, SD = 1.34), while truncation and phrase searching were also widely used. Students demonstrated moderately positive perceptions of online information, rating verifiability (M = 3.41, SD = 1.20) and timeliness (M = 3.35, SD = 1.25) relatively high. Practical implications: The study underscores the need for digital literacy workshops and targeted training on advanced search techniques to enhance students’ skills in evaluating, accessing, and effectively utilizing online information sources for academic success.